Capacity building of child support grant recipients: a case study of unemployed mothers in Katlehong Township - Onceya, Anathi (My University, 2020)
Capacity building is a paramount endeavor of improving the functioning and performance of individuals in various settings. Owing to unemployment, the functioning of people is negatively affected. Unemployment can be regarded as one of the root causes of dependency on Child Support Grant (CSG). More than twelve million South Africans benefit from CSG. Globally, countries like Brazil and Mexico introduced programmes that transfer cash to poor families to combat the impact of unemployment. The State is mandated to provide for the needs of those who cannot provide for themselves. The study explored perspectives of CSG recipients on strategies for capacity building to enhance self-reliance among unemployed CSG recipients. A qualitative research approach was adopted. A case study research design was employed and the collective case study was adopted. The population was all the unemployed CSG recipients residing in Katlehong Township. The purposive sampling technique was utilised to select participants. The sample was comprised of 32 unemployed mothers who benefittedfrom the CSG. Four focus groups; each with eight participants, were conducted to collect data. The focus group guide was utilised to facilitate the group discussions. Thematic analysis was used to analyse data. The findings revealed that multiple factors contribute to unemployment. These include lower levels in education, discrimination, availability of heavy manual labour and lack of services or support from the government. The effects of unemployment can be seen through difficulties in meeting basic needs, family dysfunction, increased levels of prostitution and poor emotional wellbeing, and thus the reliance on the CSG. Strategies for improving the capacities of individuals include access to institutions of higher learning, electricity and land, and training on farming to enable the unemployed individuals to be self-reliant. Therefore, implementation of capacity building initiatives can improve the chances of the beneficiaries to secure employment or initiate Small, Medium and Micro Enterprises(SMMEs)and promote self-reliance and self-sustainability
A report on a research study presented to The Department of Social Work School of Human and Community Development Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree Master of Arts in Social Work, 2020